Time domain linear sampling method for qualitative identification of buried cavities from elastodynamic over-determined boundary data. (June 2015) - Khaji, N.; Dehghan Manshadi, S.H.
Highlights: Time domain linear sampling method (LSM) is developed for elastic wave propagation. The LSM is an effective approach to image the geometrical features of unknown targets. This method is used in inverse acoustic problems of near-field elastic wave forms of finite media. This study exploits the LSM in the time domain analyses using spectral finite element method (SFEM). Abstract: A time domain version of linear sampling method (LSM) is developed for elastic wave imaging of media including scatterers with arbitrary geometries. The LSM is an effective approach to image the geometrical features of unknown targets from multi-view data collected from measurement of casual waves. This study emphasizes the exploitation of the LSM using spectral finite element method (SFEM). A comprehensive set of numerical simulations on two-dimensional elastodynamic problems is presented to highlight many efficient features of the proposed fast qualitative LSM identification method such as its ability to locate an inclusion (e.g., a crack) and estimate its dimensions.